Implementation of Sanctions for Violations of Coral Reef on Protection Laws - Surandi Woong Arya; Dwi Pratiwi Markus; Muhammad Ali (Unissula, 2025)
This study aims to analyze law enforcement against coral reef destruction in the waters of Raja Ampat Regency, with a focus on improving the quality of law enforcement resources, especially the Water Police Unit. The approaches used include normative legal and empirical legal approaches with descriptive-analytical methods. The research data consists of primary data obtained through interviews and secondary data from literature reviews and documentation. The results of the study show that legal norms related to coral reef protection have strict sanctions for violations. Law enforcement efforts are carried out through supervision, application of sanctions, and socialization to the community regarding the impact of destroying marine ecosystems as a criminal act. This study highlights the importance of the active role of all elements of society, including parents, in supporting the development of public security and order. This study uses a collaborative approach between law enforcement officers and the community to create legal awareness and improve the effectiveness of marine ecosystem protection in the waters of Raja Ampat. This approach strengthens the role of local culture as a means of education and supervision, creating a more adaptive and sustainable law enforcement model.